2017
DOI: 10.14814/phy2.13093
|View full text |Cite
|
Sign up to set email alerts
|

C57BL/6J mice as a polygenic developmental model of diet-induced obesity

Abstract: Susceptibility to obesity changes during the course of life. We utilized the C57BL/6J (B6) and 129S mouse as a genetic model for variation in diet‐induced obesity to define the adiposity phenotypes from birth to maturity at 8 weeks‐of‐age. From birth to 8 weeks‐of‐age, both male and female 129S mice had significantly higher fat mass and adiposity index than B6 mice, although they were not obese. After 8 weeks‐of‐age, B6 had greater adiposity/obesity than 129S mice in response to a high fat (HF). We sought to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 51 publications
(189 reference statements)
6
36
0
1
Order By: Relevance
“…As described above, mice were fed the Ulman diet from receipt to 5 weeks of age in order to promote dysbiosis that is associated with the obesity phenotype which manifests beginning 8 weeks of age [40]. At 5 weeks of age, mice were randomized to treatment groups.…”
Section: Experimental Designmentioning
confidence: 99%
“…As described above, mice were fed the Ulman diet from receipt to 5 weeks of age in order to promote dysbiosis that is associated with the obesity phenotype which manifests beginning 8 weeks of age [40]. At 5 weeks of age, mice were randomized to treatment groups.…”
Section: Experimental Designmentioning
confidence: 99%
“…A HFD was used to induce obesity since reported evidence showed that genetic models of obesity (i.e., ob/ob, db/db, and leptin/ leptin receptor-deficient mice) demonstrated resistance in developing mammary cancer (23). C57BL6 mice are particularly sensitive to DIO (24). Forty mice (n = 40) were randomly assigned into two equal groups (n = 20) and allocated one of two respective diets for 12 weeks (Figure 1).…”
Section: Diet Regimensmentioning
confidence: 99%
“…Eight-week-old inbred C57BL/6 male and female mice (n = 64) were acquired from the SAHMRI specific pathogen-free and PC2 animal facility breeding colony (Adelaide, SA, Australia) from animals originally obtained from The Jackson Laboratory (Bar Harbor, ME, USA). This strain was chosen because it is one of the most widely used inbred strains of laboratory mouse [19], particularly for metabolic studies [20]. Mice of the same sex were group housed, four to a cage, and maintained within a temperature-controlled environment (22 ± 2 • C) under a 12 h light-dark cycle with ad libitum access to food and autoclaved reverse osmosis water throughout the experiment.…”
Section: Animals and Dietary Interventionsmentioning
confidence: 99%